Hoe is de wereld eraan toe : 1991 - Brown, Lester R.; Flavin, Christopher; Postel, Sandra; Starke, Linda (Amsterdam: Milieudefensie, 1991)
"Lester R. Brown; Christopher Flavin; Sandra Postel, Linda Starke... et al. Aanwinst van De Batselier, NorbertOorspronkelijke titel : State of the World 1991"